IDENTIFIKASI HAZARDPADA PEKERJA KONTRAKTOR SIPIL DENGAN METODE CSMS DI PT. X PASURUAN - Tanti Olivina Sari (Universitas Airlangga, 2017)
Hazard is always available on every work process in the workplace and each hazard has a different level of potential hazard, and therefore needs to be done identification hazard. Contractor Safety Management System (CSMS) Program in PT. X applied to prevent and suppress the occurrence of a hazard to the civilian contractors. This study was conducted to identify the hazard to workers civilian contractors using CSMS PT. X Pasuruan. This research was an observational descriptive and presented in the narrative. Identification of hazard in stage are pre-work activities and execution of work at civilian contractor PT. X Pasuruan. The data collection method was by observation, indepth interview, and interviews. The results showed on the stage of pre-employment activities PT.1 as a civilian contractor company in cooperation with PT. X Pasuruan, meets only 14 subjects (93.3%). At the stage of implementation of the work there are two items that realization is not achieved, and at the final evaluation stage there are three items that are below 80% votes and does not meet the requirements. Risk of harm to the contractor civilians in the workplace can be prevented to a minimum, it was because a good management system in the company. Companies obedient in carrying CSMS program regulating health and safety management systems of work, by making the program a monitoring schedule for the work progresses and increasing Awareness to contractors, by providing training in occupational health and safety aspects.Keywords: identification, potential hazard